Consumption of Fat, Protein, and Carbohydrate Among Adolescent with Overweight / Obesity (Journal of Maternal and Child Health, 2019)
Background: Excessive nutritional status is a problem related to food, nutrition and public health globally which increases its prevalence quickly and can occur in all aspects of life. The increasing prevalence of excessive nutritional status is a time bomb for some countries that can explode in the future both in terms of health, mental and economic impacts for countries that are associated with increased health costs. Consumption levels such as fat, protein, and carbohydrates affect excessive nutritional status, excessive fat intake for a long time can cause overweight/obesity.Subjects and Method: The design of the study is analytic observation including a total of 111 teens who are overweight and obese. The sampling technique is a random sampling. The analysis was conducted using smart pls version 3.Results: Diet had a positive effect on overweight (b= 2.18; p= 0.032) and level of food consumption (b= 2.33; p= 0.022). High level of fat, protein, and carbohydrates consumption had a positive effect on overweight among adolescents (b= 11.54; p